Extent of late gadolinium enhancement detected by cardiovascular magnetic resonance correlates with the inducibility of ventricular tachyarrhythmia in hypertrophic cardiomyopathy - Flüchter, Stephan; Kuschyk, Jürgen; Wolpert, Christian; Dösch, Christina; Veltmann, Christian; Haghi, Dariusch; Schönberg, Stefan; Süselbeck, Tim; Germans, Tjeerd; Streitner, Florian; Borggrefe, Martin; Papavassiliu, Theano (Journal of cardiovascular magnetic resonance, 2010)
Myocardial fibrosis is frequently identified in patients with hypertrophic cardiomyopathy (HCM). The aim of this study was to investigate the role of myocardial fibrosis detected by late gadolinium-enhancement (LGE) cardiovascular magnetic resonance (CMR) as a potential arrhythmogenic substrate in HCM. We hypothesized that the extent of LGE might be associated with the inducibility of ventricular tachyarrhythmias (VT) during programmed ventricular stimulation (PVS).
Gesehen am 17.10.2023